A new species of Neuraphes Thomson, 1859 (Coleoptera: Staphylinidae: Scydmaeninae) from Kazakhstan - Hlaváč, Peter; Nakládal, Oto (Zootaxa, 2015)
Neuraphes (s. str.) kazakhstanicus, new species of the tribe Cyrtoscydmini, is described from Kazakhstan. The genus is for the first time recorded from Central Asia. A detailed morphological study is presented.